Development of Artificial Intelligence-Assisted Learning Videos to Improve Students' Understanding of Islamic History Materials - Robi’atul ‘Adawiyah; Taufiqurrahman Taufiqurrahman (Jurnal Pendidikan Islam Indonesia, 2025)
The delivery of Islamic history material in several schools, including SMK Khamas, still uses conventional methods such as lectures, which tend to be monotonous. The delivery of material through textual explanations and teacher-centered learning is less appealing to students. Furthermore, students' low interest in reading history materials, which are typically very long texts with few visuals, has resulted in a low level of understanding of the material. In response to this issue, artificial intelligence-assisted learning videos were developed with the aim of presenting the material in a more interesting and easy-to-understand manner. The main objective of this activity is to design educational videos that meet students' needs and to determine their effectiveness in improving students' understanding. The development process utilises a Research and Development (R&D) approach with a 4D model, comprising the Define, Design, Develop, and Disseminate stages. The effectiveness test was conducted by involving two departments, namely TJKT and DKV, using the Mann Whitney U Test. The test results showed a statistical value of W = 351 and a p-value = 0.0006539 (two-sided), which means that there is a significant difference in student understanding between the two departments. The one-sided (greater) test also produced a p-value = 0.0003269, indicating that the scores of students in the TJKT department were significantly higher than those in the DKV department. Based on these findings, it can be concluded that the development of AI-based learning videos effectively improves students' understanding of Islamic history material. This video is expected to be a more engaging alternative learning medium that is tailored to the needs of today's digital generation.